Participation in continuous professional development training and perceived teaching assessment: A case study at the Malaysian Technical University - Abdullah, Nor Hazana (Academic Publishing Platforms, 2018)
Participation in training has been claimed to have various effects on individuals, teams and organizations. In the context of higher education, continuous professional development (CPD) training programs is of utmost importance to improve academicians' competencies, teaching effectiveness and eventually students' performance. However, majority of studies on CPD training programs in Malaysia have been exploratory and descriptive in nature and none has investigated the relationship between participation in CPD training programs and perceived teaching performance. Thus, thus study aimed to bridge the empirical gap using quantitative secondary data from year 2015 to 2017. University's CPD training program participation records and the teaching assessment ratings by students on eighty academicians were included in this study based on the data accessibility from both sources. Descriptive analyses showed that majority of respondents who were rated excellent by students attended CPD training programs. Linear regression analysis showed that 11% of variance in teaching performance was explained by participation in CPD training programs. This finding substantiates the importance of CPD training programs. More importantly, this result shows that compulsory CPD training programs during the initial teaching years is not sufficient to maintain teaching performance. Consequently, academicians need to participate in CPD trainings to upgrade their teaching know-hows